Удосконалення структури системи захисту друкованої продукції - Киричок, Т. Ю.; Дорощук, В. Р. (ТОВ «Видавництво Ліра-К», 2025)
The object of protection is both printed securities and printed media that certify the authenticity of consumer products. Improving the system for protecting products against counterfeiting should be based on the requirements of national and international standards.
Keywords: захист друкованої продукції; друкована продукція